Special issue on linear parameter varying systems. (30th July 2014) - Edwards, Christopher; Marcos, Andres; Balas, Gary; Edwards, Christopher; Marcos, Andres; Balas, Gary
SUMMARY This special issue contains six papers on the topic of linear parameter varying systems. The papers consider quite different theoretical problems, although four are related to either fault‐detection and fault‐isolation or fault‐tolerant control. These theoretical ideas are demonstrated on applications taken from the areas of aerospace, automotive and renewable energy engineering. Copyright © 2014 John Wiley & Sons, Ltd.